2021
DOI: 10.1016/j.omtn.2021.01.028
|View full text |Cite
|
Sign up to set email alerts
|

miR-224-5p-enriched exosomes promote tumorigenesis by directly targeting androgen receptor in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is the most common form of cancer, resulting in cancer-related deaths worldwide. Exosomes, a subclass of extracellular vesicles, are produced and secreted from various types of cells, including cancer cells. Cancer-derived exosomes can deliver nucleic acids, proteins, and lipids to provide a favorable microenvironment that supports tumor growth through enhancing cell proliferation and metastasis. Our results showed that miR-224-5p was upregulated in NSCLC patient tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Previous investigations found that miR-224-5p was a circ_0017639 downstream target [ 13 ], and the increased expression of miR-224-5p was proved to inhibit cell proliferation in NSCLC [ 35 , 36 ]. PIK3R3, a regulatory subunit of phosphatidylinositol 3-kinase (PI3K) had been reported to be aberrantly expressed in some types of cancers, and the promotive effects of PIK3R3 on cell proliferation, migration, and invasion of several cancers, including NSCLC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations found that miR-224-5p was a circ_0017639 downstream target [ 13 ], and the increased expression of miR-224-5p was proved to inhibit cell proliferation in NSCLC [ 35 , 36 ]. PIK3R3, a regulatory subunit of phosphatidylinositol 3-kinase (PI3K) had been reported to be aberrantly expressed in some types of cancers, and the promotive effects of PIK3R3 on cell proliferation, migration, and invasion of several cancers, including NSCLC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miR-155 and exosomal miR-196a-5p derived from tumor-associated macrophages activated NSCLC metastasis [ 39 ]. Exosomal miR-224-5p derived from tumor cells significantly promoted the growth and metastasis of NSCLC by inhibiting AR expression [ 40 ]. miR-3180-3p-enriched exosomes reduced the progression of NSCLC by suppressing FOXP4 expression [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the activation of β -adrenergic receptors promotes tumor progression and development of resistance to treatment [ 27 , 28 ]. Fos/Jun-dependent signal transduction pathways are thought to be major effects of oncogene action in NSCLC [ 29 ]; moreover, exosome-derived miR-224-5p induced NSCLC cell proliferation and metastasis by directly suppressing AR [ 30 ]. Studies have found that vascular epidermal growth factor receptor 2 (VEGFR-2) plays a key role in the occurrence and development of tumors including NSCLC [ 31 – 33 ].…”
Section: Discussionmentioning
confidence: 99%